Effects of surface treatment on zirconia-dentine microstructure bonding interface with different particle sizes of zirconia powder - Nurul Shayhiera Aminuddin,; Nashrah Hani Jamadon,; Nurul Hannani Abdul Hadi,; Muhammad Sufiyan Amril,; Yew, Hsu Zenn (Penerbit Universiti Kebangsaan Malaysia, 2024)
Zirconia-based materials have emerged as promising resources for dental restoration applications owing to their excellent strength and aesthetic appearance. In clinical practices, surface treatment on zirconia is essential to ensure enhanced dental bonding. In this study, a novel method was used to produce zirconia block, and the influence of surface treatment on zirconia-dentine microstructure bonding interface was investigated for different particle sizes of zirconia powder. The particle sizes used in this study were 90 and 30 nm on the basis of manufacturer claims. A zirconia block of both particle sizes underwent surface treatment airborne-particle abrasion (50 μm, 0.4 MPa). Dentine specimens were prepared from extracted premolars stored in 0.1% tymol solution before being randomly cemented with the zirconia block sample by using self-adhesive resin cement (RelyX U2000 Clicker, 3M) and then light polymerised. The results after surface treatment showed higher surface roughness values for 90 and 30 nm at 0.17 and 0.18 μm, respectively, than those of the sample without surface treatment at 0.05 and 0.06 μm, respectively, showing no significant difference between particle sizes. Surface treatment improved the bonding of zirconia because the surface roughness allowed for enhanced interlocking of the cement onto the zirconia surface. However, the unbonded dentine and cement was due to the existence of a smear layer on the dentine surface that prevented the self-adhesive resin cement to work well with the dentine surface. Thus, dentine primer must be used to chemically remove the layer and allow for proper bonding between the resin cement and dentine surface.